2009
DOI: 10.1103/physrevb.79.035311
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-induced metallicity ofSrTiO3(001) surfaces: A density functional theory study

Abstract: The effect of atomic hydrogen adsorption on TiO 2 -terminated and SrO-terminated SrTiO 3 ͑001͒ surfaces is studied using density functional theory calculations. Several adsorption coverages ͑1/12, 1/6, 1/3, 1/2, 2/3, and 1 monolayer͒ are considered. It is found that the hydrogen adsorption shows site selectivity and causes remarkable surface distortion. Surface metallicity induced by the hydrogen adsorption is observed and revealed to be caused by the electron donation from hydrogen to the surface. Our results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
47
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 31 publications
6
47
0
Order By: Relevance
“…33,34 In Figure 4a, we see that the charge obtained from the adsorbed H is present mostly on the surface Ti state, which has been lowered from the middle of the conduction band and now forms its bottom; the reason for this drop in energy will be discussed in Section IV. Although all of the surface Ti d states are occupied from the local density of states (LDOS), the majority of the charge is located in the d xy band, with a lesser amount in the d yz and d xz bands, and a smaller amount still in the e g bands.…”
Section: Electronic Structurementioning
confidence: 96%
See 1 more Smart Citation
“…33,34 In Figure 4a, we see that the charge obtained from the adsorbed H is present mostly on the surface Ti state, which has been lowered from the middle of the conduction band and now forms its bottom; the reason for this drop in energy will be discussed in Section IV. Although all of the surface Ti d states are occupied from the local density of states (LDOS), the majority of the charge is located in the d xy band, with a lesser amount in the d yz and d xz bands, and a smaller amount still in the e g bands.…”
Section: Electronic Structurementioning
confidence: 96%
“…Indeed, in Figure 5b, we see an increase in charge density on the H in the Ti-H complex. This can be explained by back-donation; 34,56 the H adsorbed by O in the 1/3 ML H coverage donates charge to the system, which settles in the surface Ti d states.…”
Section: Electronic Structurementioning
confidence: 99%
“…It has been shown that the hydrogen adsorbed on the SrTiO3(001) surface forms an O-H bond [13,14]. Since hydrogen is an amphoteric element, hydrogen is possibly adsorbed to cations in addition to anions of oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…Although these features were mentioned in some studies, 17,27,28 little attention has been paid to the intrinsic surface state at the SrTiO 3 surface and its relation to the possible 2DEG. near Sr ions at the surface layer is lower than that at the middle layer, and thereby contributing to the lowering of the surface Ti d xy state.…”
mentioning
confidence: 99%
“…Another source of doping may be hydrogen adsorption on the SrTiO 3 surface. 17 Regardless of the types of defect and adsorbate, both oxygen vacancies and hydrogen adsorption actually introduce a surface doping at the SrTiO 3 surface. The attractive potential generated by the two-dimensional dopants at the surface may be an origin of creating the 2DEG.…”
mentioning
confidence: 99%